Visual Design and Reasoning with the Use of Hypergraph Transformations - Grabska, Ewa; Ślusarczyk, Grażyna; Le, Truong (Electronic Communications of the EASST, 2008)
This paper deals with visual design and reasoning. A visual language with its internal representation in the form of attributed hierarchical hypergraphs is discussed. Hypergraph attributes allow for defining and analysing constraints imposed by design knowledge. Operations on hypergraphs which reflect modifications of design diagrams are also presented. The approach is illustrated by examples of designing floor-layouts.